HISTORIOGRAFI HADIS DI MASA MUTAQADDIMIN DALAM PANDANGAN MUSTAFA AZAMI - Watukila, Slamad (Amsal Al-Qur’an: Jurnal Al-Qur’an dan Hadis, 2024)
This study examines the historiography of hadith during the Mutaqaddimin period (1st-IIth centuries AH) from the perspective of Mustafa Azami, a contemporary hadith scholar who rejects the orientalist claim that hadith were not written in the first century AH. The historical differences between the Qur'ān and hadith, as well as orientalist criticism that casts doubt on the authenticity of hadith, form the background of this study. Orientalists such as Schacht argued that hadith were only transmitted orally in the early days of Islam. Mustafa Azami, through his various researches, attempted to prove that hadith had been written and codified since the time of the Prophet and reached its peak in the second century Hijri under Caliph Umar bin Abdul Aziz. This study aims to explore the history of hadith writing and codification and to understand the contribution of scholars in maintaining the authenticity of hadith during the Mutaqaddimin period. Using a qualitative method with a literature study, the primary source used is Mustafa Azami's translation, Studies In Early Hadith Literature, as well as various related articles and books. The results showed that the writing and codification of hadith began since the time of the Prophet and was continued by the companions and tabi'in. Official codification was carried out during the time of Umar bin Abdul Aziz, followed by the development of major hadith books in the third century A.H. Azami succeeded in proving the originality of hadith since the early days of Islam, rejecting the accusations of orientalists.